INTERACTION OF DISCIPLINES OF LINGUISTIC AND LITERARY CYCLES IN THE SYSTEM CULTURAL EDUCATION OF ENGLISH STUDENTS (Pedagogy of Higher and Secondary Education, 2006)
The article dwells upon the problem of teaching Anglistics as a set o f subjects interconnected and interdependent. A plan for studying this set o f subjects at the English Language Departments of Universities is made for the whole 5-year period of studies; it takes into account possible variants of interdisciplinary ties and connections. Primary attention is paid to English-language literature as a source of variegated means of improving students' skills of philological analysis as well as a device for studying English and American mentality.